Labor market regulations and the demand for labor in Brazil - Ricardo Paes de Barros; Carlos Henrique Corseuil; Gustavo Gonzaga (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
The main objective of this study is to evaluate the impact of the 1988 changes in labor market regulations prescribed by the new Constitution on the level of employment and on the speed of employment adjustment in Brazil. From the many aspects of labor market regulations, this study concentrates on those that directly influence variable labor and dismissal costs. Evaluating the impact of changes in these costs on the level of employment and speed of adjustment is based on estimates of structural dynamic models for labor demand at different points in time before and after the 1988 constitutional change. The empirical strategy is to estimate such models from micro-longitudinal monthly data for a sample of 5,000 manufacturing establishments, which cover the period from January 1985 to December 1997. To try to isolate the effect of the constitutional change on the parameters of the labor demand function from the effects of the trade liberalization process and from the several stabilization plans that also occurred by the end of the 1980s, we regress our monthly estimates of these parameters on a temporal indicator of the 1988 constitutional change, controlling for a variety of other macroeconomic indicators.
Keywords: J23; 330